2003
DOI: 10.1128/iai.71.3.1200-1208.2003
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic Membrane Protein H Has Evolved in Parallel with the Three Disease-Causing Groups ofChlamydia trachomatis

Abstract: Chlamydia trachomatis is a human pathogen causing trachoma, urogenital disease, and lymphogranuloma venereum (LGV). A family of nine polymorphic membrane protein genes (pmpA to pmpI), resembling autotransporter proteins, has recently been discovered in C. trachomatis. pmp genes are large and predicted to be outer membrane proteins. We hypothesized that they would contain useful nucleotide sequence variability for epidemiologic studies. Since sequence information is available only for serovars D and L2, we soug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 30 publications
3
59
1
2
Order By: Relevance
“…We also found that serovars Da, E, and F evolved separately from the other urogenital serovars, as evidenced by a distant phylogenetic branch from the urogenital group. A similar branch was observed for pmpI (47). This is interesting, because serovars E, F, and D/Da are the most prevalent serovars among sexually transmitted disease populations worldwide.…”
Section: Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…We also found that serovars Da, E, and F evolved separately from the other urogenital serovars, as evidenced by a distant phylogenetic branch from the urogenital group. A similar branch was observed for pmpI (47). This is interesting, because serovars E, F, and D/Da are the most prevalent serovars among sexually transmitted disease populations worldwide.…”
Section: Resultssupporting
confidence: 50%
“…The pmpC tree revealed a separate clade that clearly distinguishes LGV serovars from all others, as was the case for pmpH. Also, ocular serovars were clustered together for pmpC, although this is more evident for pmpE and pmpH (47). We also found that serovars Da, E, and F evolved separately from the other urogenital serovars, as evidenced by a distant phylogenetic branch from the urogenital group.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…However, other serovars cause ocular trachoma or lymphogranuloma venereum. In a study that included 15 serovars representing these three disease groups, it is interesting that the PmpH family produced a tripartite tree that exactly paralleled the disease group into which a given serovar fell (123).…”
Section: Regional Trp Hot Spots Exemplified By Polymorphic Membrane Pmentioning
confidence: 99%
“…The recent completion of five chlamydial genome sequences has led to the division of the Chlamydiaceae into two genera; Chlamydia (Chlamydia trachomatis, Chlamydia suis, and Chlamydia muridarum), and Chlamydophila (Chlamydophila pneumoniae, Chlamydophila abortus, Chlamydophila psittaci, Chlamydophila pecorum, Chlamydophila felis, and Chlamydophila caviae) (77,126). However, despite these phylogenetic differences, all the species demonstrate commonalities in their life cycles, virulence traits, and modes of host and tissue tropism (77,186,469). Indeed, all members of the Chlamydiaceae possess a developmental life cycle that alternates between the infectious extracellular form termed the elementary body (EB) and the metabolically active form termed the reticulate body (RB); the EB develops into the RB after infection (186).…”
Section: Cluster 7: Chlamydial Autotransportersmentioning
confidence: 99%